Reconstruction of Topology Optimized Geometry with Casting Constraints in a Feature-Based Approach - Mayer, Johannes; Denk, Martin; Wartzack, Sandro (Proceedings of the Design Society, 2023)
Topology Optimization (TO) is an established method for the development of high strength and lightweight structural components. However, its results have to be geometrically revised to obtain a computational model that meets product development requirements. Design has to be in accordance with manufacturing constraints. Geometry reconstruction therefore still is a typically manual and tedious task, but increasingly supported by computational and automated approaches. In this paper, the inclusion of a casting constraint in an automated Medial Axis based reconstruction method is presented. Since the Medial Axis provides cross-section values by the computation of maximally inscribed spheres, this information is used for geometry reconstruction and even further for the purposeful adaption of the cross-section to match Heuver's circle method. Thereby, the directed solidification of molten material is considered. With a predefined feeder position, the demonstrator of a suspension control arm is used to show the application of the method. Resulting CAD-models are also structurally evaluated for their stiffness characteristic
Keywords: Topology Optimization; Medial Axis Transform; Computational Design Methods; Computer Aided Design (CAD); Lightweight Design